Unveiling neuroimmunology profile of immunological non-responders in HIV: a multimodal MRI approach - Zhang, Yang; Ji, Jiahao; Zheng, Luyao; Cai, Miaotian; Sun, Guangqiang; Ma, Yundong; Zhang, Xin; Chen, Xue; Zhang, Yulin; Lin, Xiao; Li, Zhen; Zhang, Tong (Frontiers in Immunology, 2024)
BackgroundPeople living with HIV (PLWH), especially immunological non-responders (INRs), may experience adverse neurologic events. However, the extent of neurological impairment in INRs remains uncertain. This study evaluates brain structure and function, immune dysregulation, and peripheral immunomarkers in INRs and immunological responders (IRs) among PLWH, classified according to immunological response criteria, within a clinical research setting.MethodsThis study utilized multi-modal MRI to assess brain structure and function in INRs (n = 25) and IRs (n = 53). Mass cytometry and Luminex/ELISA assays were employed to analyze peripheral blood monocytes, T cell subpopulations, cytokines, chemokines, neurotrophic factors, and endocrine factors.ResultsNeuroimaging findings revealed notable changes in brain structure and function in INRs, including increased fractional amplitude of low-frequency fluctuations and regional homogeneity in the left middle temporal gyrus, as well as decreased grey matter volume in the left middle temporal gyrus, left lingual gyrus, and right rolandic operculum. Furthermore, INRs exhibited significant alterations in functional connectivity in the temporal and occipital gyrus. Mass cytometry analysis demonstrated significant immune dysregulation in INRs, characterised by increased levels of senescent and activated T cells, and heightened monocyte activation. Additionally, noteworthy associations were found between neurological abnormalities and peripheral levels of immunomarkers, inflammatory cytokines, chemokines, neurotrophic factors, and endocrine factors in INRs.ConclusionThese findings underscore the associations between immune dysfunction and changes in brain structure and function, emphasizing the importance of further investigations in this field.